Cortical activity and gait parameter characteristics in people with multiple sclerosis during unobstructed gait and obstacle avoidance - Santinelli, Felipe Balistieri [UNESP]; Sebastião, Emerson; Kuroda, Marina Hiromi [UNESP]; Moreno, Vinicius Christianini [UNESP]; Pilon, Julia [UNESP]; Vieira, Luiz Henrique Palucci [UNESP]; Barbieri, Fabio Augusto [UNESP] (Elsevier, 2021)
Background: People with Multiple Sclerosis (PwMS) present higher cortical activity during walking. However, the cortical activity during gait while avoiding an obstacle is still not clear. Objective: To investigate cortical activity and gait spatial-temporal parameters in PwMS during two different gait tasks (i.e., unobstructed and obstacle avoidance). Method: Fifteen PwMS and 15 healthy controls (CG) were recruited. Participants performed ten trials in each gait condition, wearing a 64-electrode cap electroencephalogram (EEG) at 1024 Hz. Kinematic data were obtained through 10 Vicon® cameras at 200 Hz. EEG was analyzed through four cortical areas (frontal, motor, parietal, and occipital cortex areas) and five frequency bands (delta, theta, alpha, beta, and gamma) obtained through the power spectral density. In addition, spatial-temporal gait parameters (e.g., step length and velocity) were measured. Two-way ANOVA (group x gait condition) and MANOVA (group x gait condition) were used to compare gait and EEG parameters, respectively. One-way ANOVA was used to compare groups in the crossing phase of the obstacle avoidance condition. Results: PwMS presented lower step length and velocity, and higher cortical activity in frontal (beta and gamma) and parietal (gamma) cortical areas in both gait conditions compared to CG. Moreover, PwMS presented increased cortical activation (frontal and parietal) and decreased step length and velocity in obstacle avoidance compared with unobstructed gait. In addition, PwMS required more cortical resources (frontal and parietal) than CG to accomplish both gait conditions. During the obstacle avoidance task, it was further observed that PwMS positioned their feet closer to the obstacle, before and after the task, compared to CG. Conclusion: PwMS demand higher cortical resources to accomplish gait tasks, mainly when it is necessary to negotiate an obstacle in the pathway. This higher cortical activity may be a compensatory mechanism to deal with damage in subcortical structures caused by multiple sclerosis.
Keywords: Cortical activity; EEG; Gait; Motor control; Multiple sclerosis; Obstacle avoidance